If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -7 = (0.83)(x + 3) Reorder the terms: -7 + x = (0.83)(x + 3) Reorder the terms: -7 + x = 0.83(3 + x) -7 + x = (3 * 0.83 + x * 0.83) -7 + x = (2.49 + 0.83x) Solving -7 + x = 2.49 + 0.83x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.83x' to each side of the equation. -7 + x + -0.83x = 2.49 + 0.83x + -0.83x Combine like terms: x + -0.83x = 0.17x -7 + 0.17x = 2.49 + 0.83x + -0.83x Combine like terms: 0.83x + -0.83x = 0.00 -7 + 0.17x = 2.49 + 0.00 -7 + 0.17x = 2.49 Add '7' to each side of the equation. -7 + 7 + 0.17x = 2.49 + 7 Combine like terms: -7 + 7 = 0 0 + 0.17x = 2.49 + 7 0.17x = 2.49 + 7 Combine like terms: 2.49 + 7 = 9.49 0.17x = 9.49 Divide each side by '0.17'. x = 55.82352941 Simplifying x = 55.82352941
| 27=p-6 | | 2x+8=-72-8 | | 3t=5t-10 | | 111-2x=4x+7 | | 15-4x=9-7x | | -21=28+r | | 3+6x=3+x | | -15-4x=4x+7 | | 9v-81=9.9 | | 60-3x=9x+24 | | 350-3p=100+2p | | 256-5x=40x+16 | | n+13=4 | | 3x+12x=60-3x | | n+14=3 | | 2x+3x=1 | | -19=r-22 | | 4(x-1)-3(x+3)=-6 | | 2x-4=12-104 | | 6-8x=123-29x | | k+23=18 | | 0=3x^2-7x+3 | | 9=v-u | | -16t^2+96t+1=0 | | 15=-7+q | | 5x^2-15x-50=0 | | b+16=a | | 3(2x-1)=7 | | X^2=1.44 | | 3y+3=15 | | v=16u | | -2(3-x)=2(x+3) |